Stereoselective Synthesis of Protected l-allo-Enduracididine and l-Enduracididine via Asymmetric Nitroaldol Reaction - Ohsawa, Kosuke; Zhao, Hongbin; Tokunaga, Takuya; Thomas, Carys; Ganesan, A.; Masuda, Yuichi; Doi, Takayuki (Synthesis, 2020)
The diastereoselecetive and scalable synthesis of cyclic guanidine-containing nonproteinoginic amino acids, enduracididines, has been achieved. Both diastereomers, l-allo-enduracididine and l-enduracididine, were prepared via catalyst-controlled asymmetric nitroaldol reaction with the aldehyde precursor derived from l-aspartic acid. The cyclic guanidine of di-Cbz-protected l-allo-enduracididine was fully protected with an allyl group to suppress nucleophilic side reactions. Introduced allyl group was efficiently removed via π-allylpalladium chemistry without attaching the Cbz group on the cyclic guanidine moiety.
Keywords: enduracididines; nonproteinogenic amino acids; cyclic guanidines; asymmetric nitroaldol reactions; guanidine functionalization